Structural And Electronic Properties Of Transition-Metal Oxides Attached To A Single-Walled CNT As A Lithium-Ion Battery Electrode : A First-Principles Study - Liew, Weng Tack; Mohd Abid, Mohd Asyadi Azam; Raja Seman, Raja Noor Amalina (ACS Publications, 2017)
-